Pendekatan Pendidikan Matematika Realistik (PMR) Untuk Meningkatkan Komunikasi Matematika di Sekolah Dasar - Windy Aulia Sari; Zuryanty Zuryanty (Universitas Negeri Padang, 2020)
Mathematical communication in elementary schools is very low. To overcome these problems an effective approach is needed. This research of communication aims at mahtematics to improve the ability to use a realistic mathematical education approach (PMR)in the material of angular measurement in grade IV SD Kartika Kota Padang. This research is a classroom actin research that uses a qualitative and quantitative approach. Conductedin two cycles, with three meetings covering four stages, namely planning, implementation, observation, and refelction. The subjects were teacher and students of class IV SD Kartika 1-11 Kota Padang numbered 20 people. The results showed that there was an increase in the average mathematical communication sklills of students in the first cycle of 74,2 to 88,3 in the second cycle using a realistic mathematics education approach.